Species Validation of Mole Crabs Based on Molecular Marker of 16s rRNA from Bantul and Purworejo waters: Validasi Spesies Undur-Undur Laut Berdasarkan Penanda Molekuler 16s rRNA dari Perairan Bantul dan Purworejo - Nurlisa A Butet; Inge Anggraeni Bela Putri Dewi; Zairion Zairion; Agus Alim Hakim (Tropical Fisheries Management Journal, 2019)
Mole crabs live in intertidal areas of sandy beaches. Identification of aquatic species is often due misidentification cause by the cryptic phenomenon, so it is needed identification technique with a molecular approach by DNA barcoding. The study was purposed to validity and analyze kinship of the mole crabs based on 16S rRNA molecular marker from Bantul and Purworejo waters. Commercial kit of Gene Aid was used to isolation and extraction of DNA and was produced three total DNA from each location. DNA total with good quality was continued to amplified process using PCR technique with a primer of 16S rRNA. Sequence products of 16S rRNA gene were aligned with several sequences of species other from genus Emerita, Scylla, and Portunus that was found from GenBank. Species validation was performed using BLASTn. Genetic distance and phylogenetic tree were obtained MEGA 5.0 program. The samples of mole crab from Bantul and Purworejo were insignificantly different and the samples were from the same genetic sources.